Controlling the Immunological Crosstalk during Conception and Pregnancy: HLA-G in Reproduction - Lynge Nilsson, Line; Djurisic, Snezana; Hviid, Thomas Vauvert F. (Frontiers in Immunology, 2014)
In several years after its discovery in the placenta, the human leukocyte antigen (HLA) class Ib protein, HLA-G, was not given much attention, nor was it assigned great importance. As time has unraveled, HLA-G has proven to have distinctive functions and an unforeseen and possibly important role in reproduction. HLA-G is characterized mainly by its low polymorphism and restricted tissue distribution in non-pathological conditions. In fact, its expression pattern is primarily limited to extravillous cytotrophoblast cells at the maternal-fetal interface during pregnancy. Due to low polymorphism, almost the same protein is expressed by virtually all individuals. It is these unique features that make HLA-G differ from its highly polymorphic HLA class Ia counterparts, the HLA-A, -B, and -C molecules. Its function, seemingly diverse, is typically receptor-mediated, and involves interactions with a wide range of immune cells. As the expression of HLA-G primarily is limited to gestation, this has given rise to the hypothesis that HLA-G plays an important role in the immunological tolerance of the fetus by the mother. In keeping with this, it might not be surprising that polymorphisms in the HLA-G gene, and levels of HLA-G expression, have been linked to reproductive failure and pre-eclampsia. Based on recent studies, we speculate that HLA-G might be involved in mechanisms in reproductive immunology even before conception because HLA-G can be detected in the genital tract and in the blood of non-pregnant women, and is present in seminal fluid from men. In addition, HLA-G expression has been found in the pre-implanted embryo. Therefore, we propose that a combined contribution from the mother, the father, and the embryo/fetus is likely to be important. Furthermore, this review presents important aspects of HLA-G in relation to reproduction: from genetics to physiological effects, from pregnancy and pregnancy complications to a short discussion on future possible means of preventative measures and therapy.